Immiserizing Foreign Aid : The Roles of Tariffs and Nontraded Goods - Tokarick, Stephen (IMF Working Papers; Working Paper ;, 2006)
International trade theory has pointed out that factor accumulation could immiserize a country if it is sufficiently biased toward the export sector, or if it is biased toward an importcompeting sector in the presence of tariff protection. This paper analyzes the impact of aid, in the form of an increase in the capital stock used only in the nontraded sector, on real income. Yano and Nugent (1999) discussed this issue, but their analysis turned out to be incorrect. This paper demonstrates that whether aid in the form of an increase in capital specific to the nontraded sector reduces welfare depends on how aid affects the price of the nontraded good and on whether imports and the nontraded good are substitutes or complements in demand.